Estrogen protects the liver and intestines against sepsis-induced injury in rats - YEGEN, BERRAK; ŞENER, GÖKSEL (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2005)
Background and aim. Sepsis is commonly associated with enhanced generation of reactive oxygen metabolites, leading to multiple organ dysfunctions. The aim of this study was to examine the putative protective role of estradiol against sepsis-induced oxidative organ damage. Materials and methods. Sepsis was induced by cecal ligation and puncture method in Wistar albino rats. Sham-operated (control) and sepsis groups received saline or estradiol propionate (10 mg/kg) intraperitoneally immediately after the operation and at 12 h. Twenty-four hours after the surgery, rats were decapitated and malondialdehyde, glutathione levels, and myeloperoxidase activity were determined in the liver and ileum, while oxidant-induced tissue fibrosis was determined by collagen contents. Tissues were also examined microscopically. Serum aspartate aminotransferase, alanine aminotransferase levels, and lactate dehydrogenase were measured for the evaluation of liver functions and tissue damage, respectively. Tumor necrosis factor-alpha was also assayed in serum samples. Results. In the saline-treated sepsis group, glutathione levels were decreased significantly, while the malondialdehyde levels, myeloperoxidase activity, and collagen content were increased in the tissues (P < 0.01 to P < 0.001), suggesting oxidative organ damage, which was also verified histologically. In the estradiol-treated sepsis group, all of these oxidant responses were reversed significantly (P < 0.05 to P < 0.01). Liver function tests and tumor necrosis factor-a levels, which were increased significantly (P < 0.001) following sepsis, were decreased (P < 0.05 to P < 0.001) with estradiol treatment. Conclusion. The results demonstrate the role of oxidative mechanisms in sepsis-induced tissue damage, and estradiol, by its antioxidant properties, ameliorates oxidative organ injury, implicating that treatment with estrogens might be applicable in clinical situations to ameliorate multiple organ damage induced by sepsis. (c) 2005 Elsevier Inc. All rights reserved.
Keywords: estrogens; lipid peroxidation; glutathione; TNF-alpha; sepsis; LIPID-PEROXIDATION; MELATONIN TREATMENT; FREE-RADICALS; SEX-HORMONES; BURN INJURY; ANTIOXIDANT; GLUTATHIONE; STEROIDS; FAILURE; SHOCK